2005
DOI: 10.1111/j.1440-1746.2005.03604.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enhanced viscosity on canine gastric and intestinal motility

Abstract: It was concluded that enhanced viscosity delays gastric emptying, increases postprandial intestinal but not gastric motility, and has no effects on gastric or intestinal slow waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…It is well known that IDFs such as cellulose will increase in volume by absorbing water and will stimulate intestinal motility by distending the intestinal wall, whereas SDFs such as pectin are highly water soluble and make viscous solutions (gel) that facilitate the smooth transit of food from the upper to the lower intestine [20,21]. Recently, we reported that IDFs play an important role in the formation of lesions in the small intestine induced by IND in cats.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is well known that IDFs such as cellulose will increase in volume by absorbing water and will stimulate intestinal motility by distending the intestinal wall, whereas SDFs such as pectin are highly water soluble and make viscous solutions (gel) that facilitate the smooth transit of food from the upper to the lower intestine [20,21]. Recently, we reported that IDFs play an important role in the formation of lesions in the small intestine induced by IND in cats.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous report [19], we suggested that indigestible solid components of food, such as IDFs, together with NSAIDinduced intestinal hypermotility may cause damage to the surface of the intestinal mucosa when mucus is decreased. The effects of SDFs on GI motility have been studied in relation to glucose absorption, since it is well known that SDFs often cause glucose flattering [21,23]. There have been conflicting reports on the effect of SDFs on GI motility; i.e., SDFs have been shown in some studies to stimulate GI motility in humans [25], dogs [20], and pigs [26], whereas other studies have shown no effect on motility in humans [27] and dogs [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another investigation by Garcia-Casado et al used spike potential recordings made using surface electrodes to investigate and monitor intestinal mechanical activity in dogs (Garcia-Casado et al 2005). Finally, Xu et al studied the effects of enhanced viscosity on canine gastric and intestinal motility from invasive ECA and ERA recordings (Xu et al 2005).…”
Section: Motivation and Purposementioning
confidence: 99%
“…Taking into account that alloxan is an agent that selectively destroys the β-cells (Balogh et al, 2008) and decreases the endogenous insulin secretion (Yamamoto et al, 1981), our findings indicate that G. latifolium through mechanism of delayed GE may have resulted in gradual release of nutrients for absorption to match the lower levels of insulin and prevent the accumulation of excess glucose. Gastric emptying is one of the factors that affect the rate and completeness of intestinal nutrient absorption (Xu et al, 2005). "Therefore, it seems reasonable to speculate that G. latifolium attenuates blood glucose excursions partly through delayed GE, thus delaying the transfer of glucose from the stomach to the small intestine.…”
Section: Discussionmentioning
confidence: 99%